1999
DOI: 10.1024//0044-3514.30.23.165
|View full text |Cite
|
Sign up to set email alerts
|

Sexuelle Aggression zwischen Jugendlichen: Eine Prävalenzerhebung mit Ost-West-Vergleich

Abstract: Zusammenfassung: Die vorliegende Studie untersucht die Prävalenz unfreiwilliger Sexualkontakte bei älteren Jugendlichen in Ost- und Westdeutschland. 560 männlichen und weiblichen Befragten im Altersbereich zwischen 17 und 20 Jahren mit ost- bzw. westdeutschem Sozialisationshintergrund wurde eine deutsche Fassung der «Sexual Experiences Survey» vorgelegt, in der sexuelle Gewalterfahrungen weiblicher Opfer und sexuelle Aggression männlicher Täter in Abhängigkeit von verschiedenen Beziehungskonstellationen erfaßt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…The study of violence in adolescent and young couple relationships has received a good deal of attention (James, West, Deters, & Armijo, 2000; O’Keefe, 2005). In the review of international literature on intimate partner violence carried out by Krahé, Bieneck, and Möller (2005), numerous studies focus on the juvenile population (Jackson, Cram, & Seymour, 2000; Krahé & Scheinberger-Olwig, 2002; Kury, Chouaf, Obergfell-Fuchs, & Woessner, 2004). These studies show that a characteristic trait of violence dynamics in young couple relationships is the reciprocal use of violence, with the exception of sexual abuse.…”
Section: Introductionmentioning
confidence: 99%
“…The study of violence in adolescent and young couple relationships has received a good deal of attention (James, West, Deters, & Armijo, 2000; O’Keefe, 2005). In the review of international literature on intimate partner violence carried out by Krahé, Bieneck, and Möller (2005), numerous studies focus on the juvenile population (Jackson, Cram, & Seymour, 2000; Krahé & Scheinberger-Olwig, 2002; Kury, Chouaf, Obergfell-Fuchs, & Woessner, 2004). These studies show that a characteristic trait of violence dynamics in young couple relationships is the reciprocal use of violence, with the exception of sexual abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Rape (9) 0.6 0.0 0.0 0.0 0.3 36. Rape, use of alcohol (6 + 9) 5.8 1.9 1.3 2.6 0.3 NOTE: Total = sum prevalence rate; K = items according to Krahé et al, 1999; T = total; Offenders: F = steady boyfriend/husband; A = friend/colleague; B = acquaintance; U = unknown man; SI = sexual intercourse.…”
Section: Resultsmentioning
confidence: 99%
“…One fourth of the female subjects reported on incidents that may be interpreted as crimes against sexual self-determination under criminal law. This rate rises to more than 50% if incidents are included in which alcohol or drugs were used to force sexual acts (Krahé, Scheinberger, & Waizenhöfer, 1999). Lange (1998) found that 52% of girls (N = 362) had been victims of sexual harassment or violence once in their life.…”
Section: Results Of Previous Victim Surveys In Germanymentioning
confidence: 99%
See 1 more Smart Citation
“…B. Koss 1998;KrahØ et al 1999) zeigt sich, dass in weit überwiegender Anzahl die Opfer sexueller Gewalt weiblichen und die Täter sexueller Gewalt männlichen Geschlechts sind.…”
unclassified